Does play matter? Exploring Indian parental perception and its influence on childhood play - Megha Mohan; Jayashree S. Bhat (Acta Psychologica)
Play can be defined as a manifestation of purposeful states, the exemplification of consciousness created from what a child knows, and a spontaneously occurring activity. As parents are the child's first play and communication partners, their perspectives and knowledge would determine the child's early life experiences. Therefore, the present research was conducted to identify the parental perception towards play and its role in child development. Parental perception plays a vital role in the play environment they provide for their child, which in turn determines the play behaviours exhibited by their children. The present research aimed to identify the influence of parental perception towards play on the play behaviours exhibited by the child. The present research used a parental perception of the role of play in a child development questionnaire to understand parental perceptions of play. It profiled the play behaviours of children to elucidate the influence of perception over the play-based performance of children. Descriptive statistics was used to understand the parental perception towards play, and multiple regression analysis was used to identify if there was an impact of parental perception towards play on the play behaviours exhibited by their child. A significant shift in the parental belief system regarding play was observed, which revealed that parents of the present generation had a positive perception of play and valued its importance in the overall development of their children, which, in turn, influenced their children's play behaviours. This shift could be attributed to an increased awareness and parents involved in the concept of Intensive Parenting, where they are expected to have in-depth knowledge about the child's developmental stages, active involvement with their child, and invest time and efforts in an attempt to foster appropriate child development. The findings of the present research would help counsel parents to create awareness and recognise their role in promoting a conducive environment for their children to prosper in an era dominated by technology and academic pressure.